Implementasi Program Bantuan Stimulan Perumahan Swadaya (BSPS) di Desa Kantanan Kecamatan Bokat Kabupaten Buol - Polinggapo, Jefri; Mahmud, Syamsiar I (Innovative: Journal Of Social Science Research, 2025)
The need for decent housing is a basic human need that is important to improve the quality of life. The Indonesian government through the Ministry of Public Works and Public Housing (PUPR) launched the Self-Help Housing Stimulus Assistance Program (BSPS) to help low-income communities (MBR) build or repair houses to meet the standards of decent housing. This study aims to analyze the implementation of the BSPS Program in Kantanan Village, Bokat District, Buol Regency, with a qualitative descriptive approach based on Edward III's policy implementation theory. The results of the study indicate that communication mechanisms, resources, implementer dispositions, and bureaucratic structures affect the effectiveness of the program. The main obstacles include the low understanding of the community about the technicalities of the program, limited human and financial resources, and administrative obstacles at the district level. Although this program has provided positive results in improving community welfare, improvements are needed in aspects of communication, strengthening resources, and simplifying the bureaucracy to achieve better effectiveness. Keywords: implementation, policy, BSPS, decent housing, Kantanan Village